The southern Jiangsu coast is a critical moulting site for Spoon-billed Sandpiper Calidris pygmaea and Nordmann’s Greenshank Tringa guttifer - YANG, ZIYOU; LAGASSÉ, BENJAMIN J.; XIAO, HUI; JACKSON, MICHA V.; CHIANG, CHUNG-YU; MELVILLE, DAVID S.; LEUNG, KAR SIN KATHERINE; LI, JING; ZHANG, LIN; PENG, HE-BO; GAN, XIAOJING; LIU, WEN-LIANG; et al. (Bird conservation international, 2020)
The extent of intertidal flats in the Yellow Sea region has declined significantly in the past few decades, resulting in severe population declines in several waterbird species. The Yellow Sea region holds the primary stopover sites for many shorebirds during their migration to and from northern breeding grounds. However, the functional roles of these sites in shorebirds’ stopover ecology remain poorly understood. Through field surveys between July and November 2015, we investigated the stopover and moult schedules of migratory shorebirds along the southern Jiangsu coast, eastern China during their southbound migration, with a focus on the ‘Critically Endangered’ Spoon-billed Sandpiper Calidris pygmaea and ‘Endangered’ Nordmann’s Greenshank Tringa guttifer. Long-term count data indicate that both species regularly occur in globally important number in southern Jiangsu coast, constituting 16.67–49.34% and 64.0–80.67% of their global population estimates respectively, and it is highly likely that most adults undergo their primary moult during this southbound migration stopover. Our results show that Spoon-billed Sandpiper and Nordmann’s Greenshank staged for an extended period of time (66 and 84 days, respectively) to complete their primary moult. On average, Spoon-billed Sandpipers and Nordmann’s Greenshanks started moulting primary feathers on 8 August ± 4.52 and 27 July ± 1.56 days respectively, and their moult durations were 72.58 ± 9.08 and 65.09 ± 2.40 days. In addition, some individuals of several other shorebird species including the ‘Endangered’ Great Knot Calidris tenuirostris, ‘Near Threatened’ Bar-tailed Godwit Limosa lapponica, ‘Near Threatened’ Eurasian Curlew Numenius arquata and Greater Sand Plover Charadrius leschenaultii also underwent primary moult. Our work highlights the importance of the southern Jiangsu region as the primary moulting ground for these species, reinforcing that conservation of shorebird habitat including both intertidal flats and supratidal roosting sites in this region is critical to safeguard the future of some highly threatened shorebird species.